Effects of Age and Sex on Properties of Lumbar Erector Spinae in Healthy People: Preliminary Results From a Pilot Study - Wu, Zugui; Wang, Yi; Ye, Zixuan; Guan, Yingxing; Ye, Xiangling; Chen, Zehua; Li, Congcong; Chen, Guoqian; Zhu, Yue; Du, Jianping; Chen, Guocai; Liu, Wengang; et al. (Frontiers in Physiology, 2021)
Background: The influences of age and sex on biomechanical properties of paravertebral muscles have not been previously studied. Changes in the performance of paravertebral muscles biomechanical properties associated with age represent a valuable indicator of risk for lower-back-related disease. Objective: To investigate the paravertebral muscle's biomechanical properties with regard to age and sex to provide a reference dataset. Methods: We measured muscle tone and stiffness of the paravertebral muscles (at the L3–4 level) in healthy men and women (50 young people, aged 20–30 years; 50 middle-aged people, aged 40–50 years; and 50 elderly people, aged 65–75 years) using a MyotonPRO device. Results: In general, there are significant differences in muscle tone and stiffness among young, middle-aged, and elderly participants, and there were significant differences in muscle tone and stiffness between men and women, and there was no interaction between age and sex. The muscle tone and stiffness of the elderly participants were significantly higher than those of the middle-aged and young participants (P < 0.01), and the muscle tone and stiffness of the middle-aged participants were significantly higher than those of the young participants (P < 0.01). In addition, the muscle tone and stiffness of men participants were significantly higher than that of women participants (P < 0.01). Conclusion: Our results indicate that muscle tone and stiffness of the paravertebral muscles increase with age. The muscle tone and stiffness of the paravertebral muscles in men are significantly higher than in women. The present study highlights the importance of considering age and sex differences when assessing muscle characteristics of healthy people or patients.